New information about African late middle Miocene to latest Miocene (13-5.5 Ma) Hominoidea - (:unkn) unknown (My University, 2022)
In Africa, relatively few hominoid fossils are known from the late middle Miocene and late Miocene periods corresponding to the time span 13-5.5 million years ago, compared to the preceding and subsequent periods from which several thousand specimens have been reported from many different localities. In Eurasia, in contrast, many hominoid fossils are known from the Late Miocene period from diverse localities scattered from Spain in the west to China in the East. The scarcity of hominoid fossils from this period in Africa lent support to the hypothesis that the ancestors of extant African Apes and hominids may have evolved in Eurasia and then dispersed to Africa during the late Miocene where they gave rise to the extant Gorilla, Pan and Homo lineages.We herein document additional hominoid fossils from Berg Aukas, Namibia, aged ca 12-13 Ma, and rectify the locality data concerning the Niger proto-chimpanzee fossil. The new data indicate that Africa was not devoid of hominoids during the period under discussion, and they support the hypothesis that the extant African Apes and hominids may have evolved autochthonously within the continent.
Keywords: African Research